2010
DOI: 10.1039/c000750a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of oxygen on copper in Cu/HZSM5 zeolites

Abstract: The present study focuses on the characterization of the active sites for oxygen adsorption in both copper-free and copper-containing HZSM5 zeolites. FTIR, EPR, EXAFS and UV-Vis measurements offer insight into the initial state of the catalyst before oxygen adsorption. Both liquid and solid state ion exchanged samples contain a certain amount of Cu(ii) and Cu(i) ions in the alpha3, alpha4 and gamma6 position, their population ratio depending on the ion exchange temperature. They are accessible for interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 50 publications
5
38
0
1
Order By: Relevance
“…XANES measurements [16] at the copper K-edge of complex 2 confirm the oxidation state of Cu III .T wo characteristic features ( Figure 2) lead to this conclusion. Avery weak preedge peak is detected at 8980.5 eV,w hile am ore intense feature is observed in the edge at 8986.5 eV.W hereas the position of the first 1s!3d transition is an unambiguous diagnostic of Cu III ,t he more intense 1s!4p + LMCT shakedown transition is more ligand-dependent and can only support the conclusion drawn from the weak quadrupole transition.…”
Section: Introductionsupporting
confidence: 68%
“…XANES measurements [16] at the copper K-edge of complex 2 confirm the oxidation state of Cu III .T wo characteristic features ( Figure 2) lead to this conclusion. Avery weak preedge peak is detected at 8980.5 eV,w hile am ore intense feature is observed in the edge at 8986.5 eV.W hereas the position of the first 1s!3d transition is an unambiguous diagnostic of Cu III ,t he more intense 1s!4p + LMCT shakedown transition is more ligand-dependent and can only support the conclusion drawn from the weak quadrupole transition.…”
Section: Introductionsupporting
confidence: 68%
“…Due to the low concentration of 0.01 mol L −1 , several scans were conducted and averaged to increase the signal to noise ratio. Data reduction followed standard procedures given in the literature . Due to the high residual noise, Fourier filtering was applied in the range Δ r =3–11.5 Å.…”
Section: Methodsmentioning
confidence: 99%
“…Hamada et al suggested isolated, squarepyramidal Cu 2+ ions to be the active sites for the phenol formation on Cu/HZSM5 zeolites [3]. The mechanism of oxygen activation on di-copper complexes was studied for the enzyme tyrosinase [12,13], and the Cu-Cu distance in Cu/HZSM5 was found to be similar to that in tyrosinase [7], suggesting that oxidation on a zeolite may occur by the same mechanism as in the enzyme. This aspect was not in the focus of the present study which does not discriminate between and oxygen activation on dicopper complexes and on isolated ions.…”
Section: The Role Of Coppermentioning
confidence: 99%
“…Knowledge of the reaction mechanism would allow the modification of the catalysts and to increase the phenol yields. To clarify the reaction mechanism, Ene et al investigated the adsorption complexes of oxygen and benzene on the Cu/HZSM5-zeolite by spectroscopic methods [6][7][8]. The reactants mainly adsorbed on the isolated copper ions, the copper dimers and the BrØnsted acid sites, showing the presence of three possible catalytic centers.…”
Section: Introductionmentioning
confidence: 99%